Collapsing wages and rising inequality: has computerization shifted the demand for skills? - Howell, David R. (Challenge (05775132))
In the 1980s, U.S. workers were hit by falling real wages, growing shares of low-wage jobs, sharply increasing earnings inequality, and declining job benefits and job security. Many economists say that these declines in economic well-being occurred because a parallel surge in the adoption of computer technology led to a shift in demand away from unskilled jobs toward more highly skilled jobs. However, there is little evidence of a shift in the demand for skills that would be necessary to explain the remarkable wage restructuring the U.S. has experienced since 1979. Rather, what distinguishes the period since 1979 is the wholesale adoption of employment practices designed to reduce short-run labor costs. Reversing the declining real and relative wages of low-skill workers will require public policies that address worker characteristics and the ways in which wage-setting institutions work—both inside and outside the firms.